Dichloro(?5-pentamethylcyclopentadienyl)(pyridine-N)rhodium - Therrien, Bruno; Burrell, Anthony K. (My University, 2001)
Crystals of the title compd. are monoclinic, space group P21/m, with a 7.1501(14), b 13.185(3), c 8.4979(17) Å, ? 106.45(3)°; Z = 2, dc = 1.678; R = 0.017, Rw(F2) = 0.046 for 1631 reflections. The Rh atom displays a piano-stool configuration. The two halves of the mol. are related by mirror symmetry. [on SciFinder(R)]
Keywords: mol structure rhodium chloro methylcyclopentadienyl pyridine; crystal structure rhodium chloro methylcyclopentadienyl pyridine